Pembinaan SDM Dalam Membangun Keharmonisan Melalui Kegiatan Pelatihan Dosen dan tenaga Pendidik di Universitas Catur Insan Cendekia (UCIC) Cirebon - DAUD, ROSY (Jurnal Pengabdian Multidisiplin Indonesia (JUPEMI), 2024)
Improving the quality of human resources is a series of efforts to realize the whole person. It includes the development of human resources, both as people and as inseparable development resources. This PkM aims to equip education human resources with the latest knowledge and skills and develop professionalism and work ethics. The method of this coaching activity is carried out using lectures, on-the-job, vestibule, demonstration, and simulation. Human development as a development resource emphasizes humans as development actors who have a productive work ethic, skills, creativity, discipline, and professionalism, and have the ability to utilize, develop, and master science and technology (IPTEK) environmentally sound innovation and management skills. After all, the main driver of innovation is human resources and to be successful it is necessary to support, plan, and maintain a culture of innovation. Based on these aspects, the facilitator team proposed an HR development activity packaged in training for lecturers and teaching staff to build employee harmony and HR development. at educational institutions, especially at Universitas Catur Insan Cendekia (UCIC) Cirebon.